Spectroscopic, Thermal and Antioxidant Properties of Novel Mixed Ligand-Metal Complexes Obtained from Saccharinate Complexes and Azo Dye Ligand (Mnppa) - Turan, Nevin; Adigüzel R.; Buldurun, Kenan; Bursal, Ercan (Asian Network for Scientific Information, 2016)
The novel mixed ligand-metal complexes with a general formula [M(Sac)2(H2O)2L2]-nH2O] [M = Mn(II), Co(N), Ni(II), Cu(II) and Cd(N), L = 5-Methly-4-(4-nitrophenylazo)-2H-pyrazole-3-ylamine (mnppa)] have been synthesized and characterized by elemental analyses, IR, UV-VIS, magnetic susceptibility mass spectra and thermogravimetry-differential thermal analysis (TGA-DTA). Each metal (II) ion is octahedral coordinated by two sac, two mnppa and two aqua ligands. The antioxidant properties of mixed ligand-metal complexes were determined by different in vitro methods such as ABTS, DPPH, FRAP and CUPRAC assays. The results of metal complexes were compared with standard antioxidant compounds. © 2016 Nevin Turan etai.
Keywords: ABTS; Antioxidant properties; CUPRAC assays; DPPH; FRAP; Mixed ligand-metal complexes; Saccharine